PENGARUH KEMUDAHAN DAN KEAMANAN TERHADAP KEPERCAYAAN GUNA MENINGKATKAN KEPUTUSAN PENGGUNA QRIS BRI - Zella, Zella; Sismanto, Adi (UM. Bengkulu, 2025)
This study aims to analyze the influence of ease of use and security on trust to enhance the decision to use QRIS BRI among Generation Z users in the Gading Cempaka District, Bengkulu City. The data were analyzed using path analysis to examine both the direct and indirect relationships between the independent variables (ease of use and security), the mediating variable (trust), and the dependent variable (QRIS BRI user decisions). The study identifies several issues, including the low adoption rate of QRIS BRI among Generation Z due to users’ limited understanding of the payment system, concerns about data security, and a lack of transparency regarding transaction fees, which potentially reduces user trust. The results indicate that ease of use and security have a positive and significant effect on user trust, with path coefficients of 0.511 and 0.525, respectively. Furthermore, trust acts as a significant mediating variable in enhancing the decision to use QRIS BRI, with an influence coefficient of 0.624. Ease of use and security also have an indirect effect on user decisions through trust, with coefficients of 0.563 and 0.633, respectively. The impact of trust on QRIS BRI user decisions among Generation Z users in Gading Cempaka District, Bengkulu City, is reflected in the β coefficient of 0.383 (38.3%), with a significance level of 0.000 < 0.050, leading to the rejection of H0. This indicates a positive and significant effect of ease of use on QRIS BRI user decisions. Keywords: Ease of Use, Security, Trust, User Decisions, QRIS BRI